ENT 530 Social Media Portfolio: Monstr Dessert / Nur Eliani Mohd Efendy - Mohd Efendy, Nur Eliani (2020)
MONSTR, formerly known as Brownies Monster founded in 2017 is a brand under MONSTR CONFECTIONERY SDN BHD. MONSTR gained its name after a successful product Brownies Monster which leads to the production of other successful products. After receiving such great success from its product, the company decided to rebrand their brand to something more commercial and general and thus, the name MONSTR was formed. Since January 2020, the company has been using the new brand name MONSTR and the demand for MONSTR’s product keep growing day by day. The business premise is located in Jalan 9/2, Taman IKS 43650, Bangi, Selangor, Malaysia. The clients that were aimed by the business was those of the younger generations that love to eat dessert especially chocolate and also workers and students that had to stay at home during the pandemic season. The way that the product was designed enables the product to be shipped throughout Malaysia with ease and enables it to arrive at the front door of its customer safely. Thus, it is the perfect product for customers who want their dessert to arrive right at their doorstep like online distance learning (ODL) students and work from home workers. As for the business’s mission is that the business aims to expand the Monstr business throughout Malaysia and for the vision, the business wants to become a high-quality chocolatebased product manufacturer. The management of MONSTR CONFECTIONERY SDN. BHD. consists of 4 lead workers which is, the owner and also act as operational department manager, Nurul Fatin Mohamed, Nur Eliani Binti Mohd Efendy that act as the financial department manager, Adhwa Nadia Binti Nor Saidi as an administration department manager and Noor Syahirah Binti Suhaili as the marketing department manager.